2019
DOI: 10.3390/nu11102317
|View full text |Cite
|
Sign up to set email alerts
|

Intakes of Total, Free, and Naturally Occurring Sugars in the French-Speaking Adult Population of the Province of Québec, Canada: The PREDISE Study

Abstract: The objective of this study was to characterize the intakes of different types of sugars in an age- and sex-representative sample of French-speaking adults from five regions of the Province of Québec, Canada, enrolled in the cross-sectional PREDISE (PRÉDicteurs Individuels, Sociaux et Environnementaux) study (n = 1147, 18–65 years old; 50.2% women). Because only total sugar content of foods and beverages is available in the Canadian Nutrient File (CNF) 2015, the initial step of this study was thus to build a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
3
5
0
Order By: Relevance
“…Other Canadian-based studies showed similar results [ 14 , 15 , 22 , 23 ] A study by Bergeron et al 2019 in French-speaking adults ≥18 years in the province of Québec reported an average of 12%E consumption from FS, which is close to our results (11%E in adults) [ 14 ] Additionally, a study by Wang et al published in 2020, using 2015 CCHS-Nutrition data as well, estimated an average consumption of 9.9%E from FS, for Canadian adults >19 years [ 23 ]. Veugelers et al, 2020 also found similar estimates (13.3%E) of FS for Canadians using 2015 CCHS Nutrition data [ 22 ].…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Other Canadian-based studies showed similar results [ 14 , 15 , 22 , 23 ] A study by Bergeron et al 2019 in French-speaking adults ≥18 years in the province of Québec reported an average of 12%E consumption from FS, which is close to our results (11%E in adults) [ 14 ] Additionally, a study by Wang et al published in 2020, using 2015 CCHS-Nutrition data as well, estimated an average consumption of 9.9%E from FS, for Canadian adults >19 years [ 23 ]. Veugelers et al, 2020 also found similar estimates (13.3%E) of FS for Canadians using 2015 CCHS Nutrition data [ 22 ].…”
Section: Discussionsupporting
confidence: 75%
“…In general, the approaches used to estimate FS intake in all these studies are similar but appear to have a few differences [ 14 , 15 , 22 , 23 ]. One of the factors influencing the estimates is what researchers included in their definition of FS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to a contribution of 11.7 %E from free sugars in a cohort of French-speaking adults living in Quebec Canada (the PREDISE Study) [54], this analysis of 2015 CCHS-Nutrition showed a lower national average for free sugars (9.9%E), which may in part be related to a slightly different age range (19 years and older in 2015 CCHS-Nutrition as compared to 18 to 65 years old in the PREDISE Study), as well as some unique cultural traditions, lifestyle and dietary habits and food choices among Quebec residents [55,56]. Compared to sugars intake in other developed countries, added sugars intake in Canadian adults (8.6%E, 42 g/day) was about 30% lower than recent reports for American adults (13.1%E for added sugars, NHANES 2009-2012) and Australian adults (60.3 g/day for added sugars, Australian Health Survey 2011-2012) [36,57].…”
Section: Canadian Consumption Of Sugarsmentioning
confidence: 99%